2022
DOI: 10.1111/pce.14318
|View full text |Cite
|
Sign up to set email alerts
|

High safety margins to drought‐induced hydraulic failure found in five pasture grasses

Abstract: Determining the relationship between reductions in stomatal conductance (gs) and leaf water transport during dehydration is key to understanding plant drought responses. While numerous studies have analysed the hydraulic function of woody species, minimal research has been conducted on grasses. Here, we sought to characterize hydraulic vulnerability in five widely‐occurring pasture grasses (including both C3 and C4 grasses) and determine whether reductions in gs and leaf hydraulic conductance (Kleaf) during de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 94 publications
(194 reference statements)
3
14
0
Order By: Relevance
“…This finding is at odds with expectations based on the functional equilibrium theory ( Lambers, 1983 ), whereby plants are expected to increase f BNPP ( Hui and Jackson, 2006 ; Franco et al , 2020 ) and RMF ( Poorter et al , 2012 ; Eziz et al , 2017 ) in response to drought since a greater proportional biomass investment belowground can increase the acquisition of water and other soil resources ( Wilcox et al , 2015 ; Zhang et al , 2017 ; Chandregowda et al , 2022a ). The observed reduction in BNPP and f BNPP in our study might be due to the large drought effect size on aboveground physiology, such as a reduction in leaf water potential and associated impacts on overall plant C assimilation (reported in Jacob et al , 2022 ) and the resulting decrease in the availability of carbohydrates to invest in belowground production. A reduction in new C allocation belowground during drought observed in pulse-labelling studies elsewhere ( Hasibeder et al , 2015 ; R.Wang et al , 2021 ) supports our findings.…”
Section: Discussionmentioning
confidence: 63%
“…This finding is at odds with expectations based on the functional equilibrium theory ( Lambers, 1983 ), whereby plants are expected to increase f BNPP ( Hui and Jackson, 2006 ; Franco et al , 2020 ) and RMF ( Poorter et al , 2012 ; Eziz et al , 2017 ) in response to drought since a greater proportional biomass investment belowground can increase the acquisition of water and other soil resources ( Wilcox et al , 2015 ; Zhang et al , 2017 ; Chandregowda et al , 2022a ). The observed reduction in BNPP and f BNPP in our study might be due to the large drought effect size on aboveground physiology, such as a reduction in leaf water potential and associated impacts on overall plant C assimilation (reported in Jacob et al , 2022 ) and the resulting decrease in the availability of carbohydrates to invest in belowground production. A reduction in new C allocation belowground during drought observed in pulse-labelling studies elsewhere ( Hasibeder et al , 2015 ; R.Wang et al , 2021 ) supports our findings.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies have simultaneously tracked declines in K leaf and g s during drought to identify hydraulic safety margins with the assumption that reduced K leaf reflects xylem cavitation (Skelton et al, 2015); however, the rehydration kinetics method used here to quantify P88 Kleaf and P50 Kleaf does not directly measure cavitation events (Brodribb & Holbrook, 2003). Indeed, recent analyses of monocot responses to drought indicated that significant declines in K leaf can occur prior to a visual detection of cavitation events in the leaf (Jacob et al, 2022; Ocheltree et al, 2020). Thus, declines in K leaf during dehydration observed here are likely due to resistance in the extra‐xylary pathway of water transport unrelated to cavitation, such as membrane damage and leakage (Ocheltree et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…has mainly been carried out on detached branches or grass stems (Lens et al, 2013;Urli et al, 2013) and more recently on grass leaves (Jacob et al, 2022;Ocheltree et al, 2016), as a marker of xylem embolism resistance. However, as plant dry-down time was found to be unrelated to embolism resistance, it is now advocated to consider rooting depth that determines plant water availability and survival times .…”
Section: Measuring Dehydration Tolerance To Assess Drought Survivalmentioning
confidence: 99%
“…The coexistence influence trait expression and phenotypes of associated plants (terHorst et al, 2018; Wang & Callaway, 2021), impacting their adaptation to drought (Zenes et al, 2020). Furthermore, biodiversity is increasingly recognized to buffer plant communities against the negative impacts of climate extremes (Isbell et al, 2017; Loreau et al, 2021) like drought (Wagg et al, 2017; Wright et al, 2021) due to positive plant–plant interactions (e.g., facilitation) and complementarity effects among plants (e.g., niche difference), which together have a potentially positive effect (i) on plant survival during drought and (ii) on plant recovery after the drought (Haberstroh et al, 2021). However, few studies have assessed how positive or negative interactions between neighbouring plants directly affect plant dehydration tolerance, drought survival and drought recovery (Griffin‐Nolan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%